Incidence, determinants and outcomes of pregnancy‐associated hepatitis B flares: A regional hospital‐based cohort study. (30th September 2017) - Kushner, Tatyana; Shaw, Pamela A.; Kalra, Ankush; Magaldi, Lora; Monpara, Pooja; Bedi, Gurneet; Krok, Karen; Centkowski, Sierra; Dalldorf, Katherine; D'souza, Julia; Halegoua‐De Marzio, Dina; Goldberg, David S.; et al.
Abstract: Background & Aims: There is limited knowledge about hepatitis B virus (HBV) flare among pregnant women. We evaluated the incidence, determinants and outcomes of HBV flare in a multicultural cohort of pregnant HBV‐infected women in the United States. Methods: We performed a retrospective cohort study of pregnant hepatitis B surface antigen‐positive women cared for at hospital‐based clinics of 4 medical centres in Southeastern Pennsylvania from 2006 to 2015. The main outcome was incident HBV flare (alanine aminotransferase [ALT] ≥2 times upper limit of normal) during pregnancy or within 6 months after delivery. Among patients with flare, we determined development of jaundice (total bilirubin ≥2.5 mg/dL) and hepatic decompensation. Multivariable logistic regression was used to estimate odds ratios (ORs) of HBV flare for risk factors of interest, including timing of flare (during pregnancy versus post‐delivery), nulliparity, younger age, HBV e antigen (HBeAg) status, and lack of anti‐HBV therapy. Results: Among 310 pregnant predominantly African HBV‐infected women with 388 pregnancies, the incidence of HBV flare was 14% (95% CI, 10‐18%) during pregnancy and 16% (95% CI, 11‐24%) post‐delivery. Jaundice developed in 12% and hepatic decompensation in 2%. Positive HBeAg was associated with HBV flare (OR, 2.55; 95% CI, 1.04‐6.20). HBV DNA was measured in 55% of patients, and only 50% were referred for HBV specialty care. Conclusions: Pregnancy‐associated hepatitis B flare occurred in 14% during pregnancy and 16% post‐delivery and rarely led to hepatic decompensation. Positive HBeAg was the main risk factor identified. Women did not have adequate HBV monitoring or follow‐up during pregnancy.